Biopolymer membranes and films : health, food, environment, and energy applications - Agostini de Moraes, Mariana; Silva, Classius Ferreira da; Vieira, Rodrigo Silveira (Elsevier, 2020)
Presents the latest techniques for the design and preparation of biopolymer-based membranes and films, leading to a range of cutting-edge applications. The first part of the book introduces the fundamentals of biopolymers, two-dimensional systems, and the characterization of biopolymer membranes and films, considering physicochemical, mechanical and barrier properties. Subsequent sections are organized by application area, with each chapter explaining how biopolymer-based membranes or films can be developed for specific innovative uses across the health, food, environmental and energy sectors. This book is a valuable resource for researchers, scientists and advanced students involved in biopolymer science, polymer membranes and films, polymer chemistry and materials science, as well as for those in industry and academia who are looking to develop materials for advanced applications in the health, food science, environment or energy industries. Key Features: Presents detailed coverage of a range of novel applications in key strategic areas across health, food, environment and energy. Considers the difficulties associated with two-dimensional materials. Assists the reader in selecting the best materials and properties for specific applications. Helps researchers, scientists and engineers combine the enhanced properties of membranes and films with the sustainable characteristics of biopolymer-based materials.--Provided by publisher.